Valorization of tannin rich triphala waste for simultaneous tannase and gallic acid production under solid state fermentation by Aspergillus niger - Pattarabhorn Pakaweerachat; Teerin Chysirichote (Chemical Engineering Communications, 2022)
This research aimed to study gallic acid production by the activity of tannase secreted by Aspergillus niger ATCC 16888 under solid-state fermentation using Triphala waste. Gallic acid is commonly extracted from Triphala using hot water. The residue contains a high number of hydrolyzable tannins. The parameters for the SSF were studied which included a nitrogen supplementary with an aeration supply. Results indicated that Triphala waste (TW) was a good substrate for valorization with tannase and gallic acid production by A. niger. When the fermentation was supplemented with 0.75% sodium nitrate that combination provided the highest biomass, tannase and gallic acid concentrations of 254.2 ± 15.4 mg g−1DS, 49.4 ± 2.0 U g−1DS and 13.3 mg g−1DS, respectively, while the aeration at 0.3 vvm (0.75% sodium nitrate supplementary) provided the highest biomass tannase and gallic productions of 445.0 ± 43.0 mg g−1DS, 53.3 ± 5.3 U g−1DS and 168.5 ± 5.0 mg g−1DS, respectively. The results indicated that the number of nitrogen atoms and the rate of aeration had significant parameters for tannase production. The carbon/nitrogen (C/N) ratio of the substrate correlated with tannase production of A. niger. The optimum C/N ratio of the substrate for tannase production was approximately 20.
Keywords: Tannin, Tannase and Anticancer Activities; Chromium effects and bioremediation